Is there any correlation between duration of vomiting before pyloromyotomy and eradication of symptoms after pyloromyotomy in hypertrophic pyloric stenosis? - Saeid Aslanabadi (Iranian Journal of Pediatric Surgery, 2016)
Introduction: Hypertrophic pyloric stenosis (HPS) is among common GI disorders in young infants, with an incidence of 1-2:1000 live births in the world. In this study, we wanted to investigate the correlation between duration of symptoms before surgery and eradication of symptoms after pyloromyotomy in HPS.